Morphological and molecular identification of Beauveria bassiana from agricultural soils (Mongolian Journal of Agricultural Sciences, 2019)
The soil environment is an important reservoir for a wide variety of entomopathogenic fungi, which can significantly contribute to the control of insect populations, especially on agricultural pests. Comparison of entomopathogens with conventional chemical pesticides, there are advantages in using biological control agents, such as human safety and other non-target organisms; pesticide residues are minimized in food and biodiversity increased in managed ecosystems. The main objective of this study was to detect and identify the entomopathogenic fungi from agriculture soils based on morphological and molecular identification. Total of 115 soil samples were collected in spring (before sowing) from different crop fields in “Unjin” and “Nart” Research and Education Centers of the university, which are located in Bornuur sum, Tuv Province from 2016 to 2018. Isolation of entomopathogenic fungus, Вeauveria bassiana was isolated using Dilution plate method in Peptone Dextrose Agar Yeast. Based on microscopic observation, hyphae branched and formed conidiogene cells, and single cell В. bassiana conidium was round and tend to oval with hyaline color. Colonies on PDAY were white to pale yellow and sometimes red pigments in reverse. Using PCR method with primer specific for identification В. bassiana, molecular analysis confirmed that all six isolates has same size of band which, appeared on agarose gel.